2008
DOI: 10.1210/en.2008-0770
|View full text |Cite
|
Sign up to set email alerts
|

Amylin-Mediated Restoration of Leptin Responsiveness in Diet-Induced Obesity: Magnitude and Mechanisms

Abstract: Previously, we reported that combination treatment with rat amylin (100 microg/kg.d) and murine leptin (500 microg/kg.d) elicited greater inhibition of food intake and greater body weight loss in diet-induced obese rats than predicted by the sum of the monotherapy conditions, a finding consistent with amylin-induced restoration of leptin responsiveness. In the present study, a 3 x 4 factorial design was used to formally test for a synergistic interaction, using lower dose ranges of amylin (0, 10, and 50 microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(151 citation statements)
references
References 34 publications
7
142
1
1
Order By: Relevance
“…Two amylin doses (5 and 10µg/kg/day) were chosen based on pilot studies, on circulating levels of DIO rats observed in Experiment 1, and on published work [16,22], and were compared to saline infused controls.…”
Section: Experiments Two: Does Chronic Elevation Of Peripheral Amylin mentioning
confidence: 99%
See 2 more Smart Citations
“…Two amylin doses (5 and 10µg/kg/day) were chosen based on pilot studies, on circulating levels of DIO rats observed in Experiment 1, and on published work [16,22], and were compared to saline infused controls.…”
Section: Experiments Two: Does Chronic Elevation Of Peripheral Amylin mentioning
confidence: 99%
“…It is known that a co-infusion of amylin and leptin reduces body weight and adiposity synergistically in DIO prone rats [22]. Additionally, it has been shown that peripheral administration of amylin restores leptin sensitivity in obese rats and humans [33].…”
Section: Amylin-induced Suppression Of Energy Intake Is Decreased Aftmentioning
confidence: 99%
See 1 more Smart Citation
“…81 The effect of the amylin/leptin combination on energy balance appeared to be paralleled by a preferential oxidation of fat as indicated by the low respiratory quotient in both the amylin/leptin and pair-fed groups; 81,[84][85][86] importantly, the lower respiratory quotient was still evident in amylin/leptin coinjected animals during the weight stable phase and not only during weight loss like in the pair-fed group. 81,85,[90][91][92] All effects combined, the amylin/leptin combination treatment prevented the suppression of energy metabolism that is typically seen in situations of negative energy balance which may, for example, be induced by simple dieting.…”
Section: Interactions Of Amylin With Other Factors Involved In the Comentioning
confidence: 95%
“…81 In other words, amylin, which itself is still effective in obese rats, 3,82,83 reduced eating and body weight significantly more when leptin was co-administered with amylin. 81,[84][85][86] The effect of amylin on leptin's action and leptin sensitivity appeared to be specific to amylin 81 because the effects were not seen to the same extent with the GLP-1 analog AC3174, 81 or when infusions of leptin were combined with the GLP-1 receptor agonist exendin-4. 87 Leptin combined with GLP-1 analogs did produce the stronger effects on eating and body weight than single compounds, but the interaction seemed to be (mathematically) additive rather than synergistic.…”
Section: Interactions Of Amylin With Other Factors Involved In the Comentioning
confidence: 99%